Non-intuitive Behavior of Polymer-Ciprofloxacin Nanoconjugate Suspensions: a Tool for Flexible Oral Drug Delivery - (:unkn) unknown (Spinger, 2021)
Ciprofloxacin (CPX) is prone to spontaneous self-aggregation and formation of supramolecular dimers (π − π stacking) due to its complicated surface chemistry which has been associated with its anomalous solubility and instability in aqueous systems particularly near neutral pH. The surface characteristic of ciprofloxacin was modified through non-intuitive counterion interaction between CPX and diethylaminoethyl dextran (DDEX) to form nanoconjugate assembly. The CPX-DDEX nanoconjugate was confirmed by FTIR, SEM, DSC, TGA, and 1H-NMR. The DSC thermograms showed a remarkable 20% reduction in the melting temperature (Tm) of CPX from 268.57±1.11°C to 214.36±1.0211°C and 78% reduction in enthalpy of fusion (ΔHf) from 59.84 kJ/mol (180.59 J/g) to 12.90 kJ/mol (38.92 J/g), indicating increased solubility and dissolution efficiency. DDEX polymer alone exhibited pseudoplastic characteristics however with more viscous rather than elastic response, while the CPX-DDEX nanoconjugate suspensions exhibited remarkable elastic behavior with significantly increased storage modulus (G′) thus controlling and extending the release of CPX. The reconstituted freeze-dried CPX-DDEX nanoconjugate suspension was chemically stable throughout the 90-day study both in the refrigerator and at controlled room temperature, while the aqueous suspension of pure CPX without DDEX was only stable for 72 and 24 h, respectively. The dissolution efficiency of the CPX-DDEX nanoconjugate suspensions increased with increasing molar concentration of DDEX to a maximum of 100% at 50 μM of DDEX followed by a remarkable decrease within the 3-week study. It was apparent that the dissolution efficiency was governed by a critical balance between the CPX solubility and the viscoelastic characteristics of the polymeric nanoassembly. This study demonstrates the potential application of polymer-drug nanoconjugation formulation design to stabilization and flexible delivery of CPX from aqueous suspension systems.
Keywords: ciprofloxacin molecular stacking; diethylaminoethyl dextran; nanoconjugate suspension; non-intuitive behavior; sedimentation volume; in vitro drug release kinetics; University of Lagos; ACEDHARS; ACE: Drug Research, Herbal Medicine Development and Regulatory Science